ENERGY AND MACRONUTRIENT RECOMMENDATIONS FOR FEMALE SOCCER ATHLETES: WHAT SPORT PRACTITIONERS MIGHT BE INTERESTED TO KNOW - Khutso Matlaila Ramokolo; Sylven Masoga; Sefora Hazel Makuse (Scientific Publishing House. NSA Press, 2024)
Female soccer sport is recently gaining popularity across the world. However, there remains little research on nutritional recommendations devoted to this group. This can pose a challenge for sports and health practitioners when conducting interventions in this group. A few authors suggested nutritional recommendations for energy and macronutrients close or similar to those used in males, usually around 7 - 12 g/kg/day for carbohydrates, 1.2 -1.7 g/kg/day for protein, 0.5 - 1 g/kg/day for fat and different resting energy expenditure formulas for energy. Still, these recommendations have not been made quite clear or at least emphasized for use amongst female soccer athletes, including the timing of these macronutrients before, during, and after training or competition. Noting the physiological and body composition differences between males and females, this review aims to explore available nutritional recommendations for female athletes so that they, coaches, and sports practitioners have a clear guide for adherence during training and intervention sessions.